New Applications of the Comet Assay: Comet-FISH and Transcription-Coupled DNA Repair - Spivak, Graciela (2008)
Transcription-coupled repair (TCR) is a pathway dedicated to the removal of damage from the template strands of actively transcribed genes. Although the detailed mechanism of TCR is not yet understood, it is believed to be triggered when a translocating RNA polymerase is arrested at a lesion or unusual structure in the DNA. Conventional assays for TCR require high doses of DNA damage for the statistical analysis of repair in the individual strands of DNA sequences ranging in size from a few hundred bases to 30 kb. The single cell gel electrophoresis (Comet) assay allows detection of single-or double-strand breaks at a 10 to 100-fold higher level of resolution. Fluorescence in situ hybridization (FISH) combined with the Comet assay (Comet-FISH) affords a heightened level of sensitivity for the assessment of repair in defined DNA sequences of cells treated with physiologically relevant doses of genotoxins. This approach also reveals localized susceptibility to chromosomal breakage in cells from individuals with hypersensitivity to radiation or chemotherapy. Several groups have reported preferential repair in transcriptionally active genes or chromosomal domains using Comet-FISH. The prevailing interpretation of the behavior of DNA in the Comet assay assumes that the DNA is arranged in loops and matrix-attachment sites; that supercoiled, undamaged loops are contained within the nuclear matrix and appear in Comet “heads”, and that Comet “tails” consist of relaxed DNA loops containing one or more breaks. According to this model, localization of FISH probes in Comet heads signifies that loops containing the targeted sequences are free of damage. This implies that preferential repair as detected by Comet-FISH might encompass large chromosomal domains containing both transcribed and non-transcribed sequences. We review the existing evidence and discuss the implications in relation to current models for the molecular mechanism of TCR.